Simulation Modeling of Train Movement at Railway Stations Using Anylogic (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the issue of simulation modeling of train movement through railway stations in order to create a testing environment and create conditions for analyzing capacity and other indicators of the railway site.